Nutritional requirements of digestible methionine+cystine for laying Japanese quails - Oliveira, Jamilly Lima Ferreira; Silva, Yasmin Maria Nunes; Rangel, Eloisa de Souza; Holanda, Mônica Calixto Ribeiro de; Lucena, Leandro Ricardo Rodrigues de; Holanda, Marco Aurélio Carneiro de (Acta Scientiarum. Animal Sciences, 2025)
The objective of the present research is to determine optimal levels of digestible methionine+cystine to maximize the laying percentage and to improve the food conversion per egg mass of Japanese quails (Coturnix coturnix japonica). The experimental period was divided into three evaluation cycles, using 175 Japanese quails in the laying phase, with an initial age of 60 days, distributed in a completely randomized design, with five treatments and five replications. The treatments consisted of five levels of methionine+digestible cystine (0.742; 0.842; 0.942; 1.042; 1.142%). The performance variables measured were: daily feed consumption, average egg weight, laying percentage and feed conversion per egg mass. For the three evaluation cycles there was no difference in daily feed consumption and average egg weight, while the laying percentage and feed conversion per egg mass showed a quadratic behavior with a peak egg laying percentage of 97.81% and minimum feed conversion per egg mass of 2.39. Level of methionine+cystine necessary to obtain a peak in laying percentage is 0.942%, which provides better feed conversion rates for birds, with methionine+cystine consumption estimated between 253 mg/bird/day and ratio methionine+cystine/lysine of 0.836 %.